Department Budgeting and Resources - Don Chu (Academic Chairpersons Conference Proceedings, 2016)
In this interactive session, we will look at the three keys to managing the budget and increasing resources for your department. First, chairs need to understand their budgets and how budgets are constructed. Next, chairs can manage their budgets, increase department productivity and work with their deans to invest resources in the department. Lastly, chairs can take steps to increase resource flow into their department
Keywords: keys to managing the budget and increasing resources for your department